An overview of practices of business social responsibility (bsr) in nigeria: a conceptual review - Gorondutse , Abdullahi Hassan; Hilman, Haim (Journal of Management and Science, 1970)
The main objective of this paper is to explore the nature of social responsibility practices in Nigeria. The paper provides a contribution to the literature by reviewing previous business social responsibility (BSR) practices around the world. The research is conceptual in nature. Finally the studies discover that bureaucratic and institutional affect the implementation of many BSR initiatives in Nigeria.